4(6z-1)-2(z+6)=9(z+1)

Simple and best practice solution for 4(6z-1)-2(z+6)=9(z+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6z-1)-2(z+6)=9(z+1) equation:


Simplifying
4(6z + -1) + -2(z + 6) = 9(z + 1)

Reorder the terms:
4(-1 + 6z) + -2(z + 6) = 9(z + 1)
(-1 * 4 + 6z * 4) + -2(z + 6) = 9(z + 1)
(-4 + 24z) + -2(z + 6) = 9(z + 1)

Reorder the terms:
-4 + 24z + -2(6 + z) = 9(z + 1)
-4 + 24z + (6 * -2 + z * -2) = 9(z + 1)
-4 + 24z + (-12 + -2z) = 9(z + 1)

Reorder the terms:
-4 + -12 + 24z + -2z = 9(z + 1)

Combine like terms: -4 + -12 = -16
-16 + 24z + -2z = 9(z + 1)

Combine like terms: 24z + -2z = 22z
-16 + 22z = 9(z + 1)

Reorder the terms:
-16 + 22z = 9(1 + z)
-16 + 22z = (1 * 9 + z * 9)
-16 + 22z = (9 + 9z)

Solving
-16 + 22z = 9 + 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
-16 + 22z + -9z = 9 + 9z + -9z

Combine like terms: 22z + -9z = 13z
-16 + 13z = 9 + 9z + -9z

Combine like terms: 9z + -9z = 0
-16 + 13z = 9 + 0
-16 + 13z = 9

Add '16' to each side of the equation.
-16 + 16 + 13z = 9 + 16

Combine like terms: -16 + 16 = 0
0 + 13z = 9 + 16
13z = 9 + 16

Combine like terms: 9 + 16 = 25
13z = 25

Divide each side by '13'.
z = 1.923076923

Simplifying
z = 1.923076923

See similar equations:

| 7p^2-54p-16=0 | | 7x+y=-28 | | 9x^3+6x^2-6x-2=0 | | 5(3x+2)-2=4(4x-30) | | 2+7(x-5)=9-7(x-5) | | 3(6x+2)=9(2x-2) | | -a/6-(31)=64 | | Z^2-2z+11=0 | | 5x^5+9x^3-x+1=0 | | 9=4g-3 | | 12y-8y=32 | | 5x^2-269=51 | | 13+2.50h=11+3.75h | | (s+4)(s-3)=0 | | 4x+5x+9=16 | | 232=75-w | | Log(9)(x^2-6)=Log(9)(30) | | c=108x^2+108xy^2 | | -7-2x=-4 | | 4k(k+5)=0 | | 19-4j=11 | | 14=8+3k | | 5*x^3-3*x^2+8=0 | | 2r(r-4)=0 | | 12-4x-9-3x= | | 3/4x-1/2=181/4 | | 2-4x-9-3x= | | 5*x^3-3*x^2-8=0 | | 4x-5(2x-9)=6(x+5)+3 | | 10+3h=19 | | c=(6x+6y^2)18x | | 2(x-6)+4x+7=43 |

Equations solver categories